Determination of Telemedicine Use Based on Financial Factors, Organizational Rules, and Technological Infrastructure - Lestari, Yuni; Warsini, Warsini; Kristanto, Budi; Kurniawan, Hendra Dwi (CV. Civiliza Publishing, 2025)
Technological developments contribute significantly to advances in the field of health, including the emergence of e-health as a digital-based health information service. With the majority of the population owning smartphones, telemedicine is a solution to overcome limited health resources through audio, visual communication, and remote discussions. There are factors that influence the implementation of telemedicine, namely financial factors, organisational rules and regulations, and technological infrastructure. The purpose of this study was to determine the use of telemedicine and describe the factors that influence the use of telemedicine in the community. This study is a correlational analytic study with a cross sectional approach. The population in this study were all families (head of family) in Jatimulyo Village. The sample in this study used all families with total sampling technique. Bivariate analysis using chi-square test. The results showed statistically between financial factors on the use of telemedicine (p=0.026), regulatory factors and organisational rules on the use of telemedicine (p=0.000), technological infrastructure factors on the use of telemedicine (p=0.019). The results of this study indicate that there is an influence between financial factors on telemedicine, organisational rules and regulations factors on the use of telemedicine, technological infrastructure factors on telemedicine